Study of Blending Fly Ash with Potentially Acid Forming Material to Prevent Acid Mine Drainage. (July 2020) - Firman; Haya, A; Alkatiri, H
Abstract: Acid Mine Drainage (AMD) is one of environmental concerns of mining activities and need to be prevented. One of AMD prevention method is passive method by blending PAF Material with Non-Acid Forming Material. One of constraint often faced by mining companies is the limitation of NAF material. Other Non-Acid Forming Material that is available and abundant near mine site is fly ash from Mine-Mouth Coal-Fired Power Plant Banjarsari. The Study of usage of fly ash as a blending material with PAF material in order to prevent AMD is deemed necessary. Different blending simulations of varying PAF material size (fine and coarse) and varying fly ash-PAF Material ratio (2:1; 1:1; and 0, 5:1 by weight) are made and leachate water from kinetic test is physically and chemically tested. This study result shows that variation in OB-Claystone grain size is not influencing the acidity of leachate water. Blending FA with OB-CS with minimum ratio of 1, 12:1 (by weight) is effective to prevent AMD generation. Acid-base equilibrium is met when ratio of mole-transfer between neutralizing mineral (periclase, lime and gypsum) to acid-generating mineral (pyrite) is 1:1 (by weight). The higher ratio of FA in blending, the lower oxidation and alkalinity-production rate. Rate of oxidation of pyrite and alkalinity-production rate is the same at OB-CS and FA blending ratio of 1:1, 62 (by weight).